The Technological Card of Using the Contextual Training for the Future Teachers’ Professional Preparation - Shapran, Olga (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The article reflects the fundamentals and principles of contextual training, its advantages over the traditional system of education at higher school and tactical role of the teacher in the management of contextual training. The author discusses the general activities of students and teachers in the context of learning. This gives you the opportunity to provide training in higher education on the basis of subject – subject relations, finding new methodological approaches to the training of future teachers. In this article the author focused on organization of students’ quasi-professional activities. The novelty of the research is characteristic stages of the contextual training in preparation of future teachers. The author developed technological card of contextual training for future teachers.